Pengaruh Ukuran Testis Terhadap Kualitas Semen Babi Landrace Dan Babi Duroc - Yoha Raldi Nadja; Cynthia Dewi Gaina; Nancy D F K Foeh (Jurnal Veteriner Nusantara, 2021)
The objective of this study was to determine the effect of testicular size on spermatozoa quality from landrace pigs and duroc pigs that had mature with age ranging 2-4 years. The macroscopic and microscopic data obtained from this study will be analyzed descriptively and for the effect of testicular size on spermatozoa quality tested using complete randomized design (RAL) using ANOVA. The results showed the average of the observations of landrace pig cement on macroscopic basis as follows: volume obtained 236.7 ml, consistency dilute, milk white, pH 7 and has the smell of a pig. Based on the variance test, the average of spermatozoa is 82.5%, spermatozoa viability is 88.6%, 12.9% abnormality and spermatozoa concentration of 215 x 106 cells / ml. The mean size of testes of landrace pig and duroc pig is calculated using excel application and testicular area calculated using PxL formula. The results obtained were as follows: left testis length of landrace pork 12.66 ± 3cm, right testis length 14 ± 1cm, left testis pavement landrace 7.66 ± 2.081cm, right testis width 8 ± 0cm with left testis area and right testis of landrace pigs respectively 96.97cm and 112cm. Duroc pigs have a length of left and right testis respectively 16.66 ± 5.507cm and 13.66 ± 3.21cm, the left and right testis widths of 83 ± 2.020cm and 8.5 ± 1.5cm respectively and the size of the left and right testis respectively are 147.1cm and 116.11cm. So tu sum up the testicular size significantly affected the semen volume produced by a pig and the size of the testes had no significant effect on motility, viability, concentration, abnormality, color, consistency, pH and odor.